Low-Field Magnetic Resonance Imaging - Klein, Hans-Martin (RöFo : Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebende Verfahren, 2020)
Abstract Background For more than two decades, the focus of technological progress in MRI was restricted to systems with a field strength of 1.5 T and higher. Low- and mid-field MRI systems, which offer some specific advantages, are vanishing from the market. This article is intended to initiate a re-evaluation of the factor ‘field strength’ in MR imaging. Method Literature review was carried out using MEDLINE database (via Pubmed) over a time span from 1980 to 2019 using free-text and Medical Subject headings (MeSH). Article selection was based on relevance and evidence. Results and Conclusion Low-field MR systems are meanwhile rare in clinical imaging. MRI systems with a lower field strength provide a reduced signal-noise ratio (SNR) and spectral differentiation. However, these systems offer a variety of advantages: Shorter T1 relaxation, better T1 contrast, fewer metal artifacts, reduced susceptibility and chemical shift artifacts, fewer dielectric effects, better tissue penetration, less RF-power deposition, fewer ‘missile effects’, reduced effect on biomedical implants such as shunt valves, less energy and helium consumption. If we free ourselves from the constraints of high-field strength, we are able to offer multiple medical, economic and ecologic advantages to our patients. The development of high-quality low-field MRI is possible and necessary. Key Points: